KONSEP PENDIDIKAN ISLAM DALAM MAQASID AL-SYARI’AH - Muh. Haras Rasyid (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
Allah Swt. created man and put out of the belly of his mother, not knowing anything, but Allah. giving the potential to learn something. Through education, a person develops this potential, know something that is around. To that education is understood as a place to embed something in a person, whether physical or spiritual nature is very important. The problem is, how it relates to maqasyidu al-Shari'ah. Education and training in addition to meaningful guidance also contains elements of "nurture". In maqasyidu al-Shari'ah, there are five things that need to be maintained, ie to preserve the religion, life, intellect, wealth and offspring. Fifth it as something that is to be the subject and object of education, whether related to meaning, the basis and objectives as well as those related to the implementation of education.